2017
DOI: 10.1007/s10750-017-3454-2
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use and preference of adult perch (Perca fluviatilis L.) in a deep reservoir: variations with seasons, water levels and individuals

Abstract: Perch Perca fluviatilis is a widespread predator in European reservoirs, frequent in open waters but also known to spend a lot of time in the littoral zones. To get insight into how adult perch used and selected their habitat in an environment subject to water level fluctuations, 21 perch were continuously tracked using acoustic telemetry over 2 years in the Bariousses reservoir (France). The different available habitats were characterized by depth classes and substrate types, presence of emerging trees, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 87 publications
(114 reference statements)
0
22
0
Order By: Relevance
“…At most sites a single pool was sampled from either the main river channel or isolated pool, with sampling focussed on areas containing vegetation (i.e. redfin perch habitat) (Lintermans, 2007; Westrelin et al., 2018). If vegetation was lacking or difficult to access, samples were collected at approximate evenly spaced intervals around the edge of the pool.…”
Section: Methodsmentioning
confidence: 99%
“…At most sites a single pool was sampled from either the main river channel or isolated pool, with sampling focussed on areas containing vegetation (i.e. redfin perch habitat) (Lintermans, 2007; Westrelin et al., 2018). If vegetation was lacking or difficult to access, samples were collected at approximate evenly spaced intervals around the edge of the pool.…”
Section: Methodsmentioning
confidence: 99%
“…Even relatively large water bodies up to several hundreds of hectares can be fully covered by positioning systems [20,307] to provide fine-scale positioning of both predator and prey over long periods of time that can be used to answer a variety of questions related to predator-prey interactions. For example, Jacobsen et al [134] identified alternative foraging strategies in acoustically tagged Eurasian perch in mesotrophic and hypereutrophic conditions.…”
Section: How Does the Distribution Of Prey Impact Movement?mentioning
confidence: 99%
“…Understanding roles and identifying pathways through which ecosystem services are generated is therefore a key question to ecology, albeit one that has been afforded less consideration in the context of movement ecology [117]. In lakes, productivity scales with the perimeter/area ratio, suggesting that small lakes, rather than great lakes or seas, would be ideal venues for investigating habitat coupling and ecological roles with replicated whole lake experiments including manipulations of the fish assemblage and experimental alterations of lake productivity [257,307].…”
Section: Can Movement Data Provide Information On the Ecosystem Role Of Megafauna?mentioning
confidence: 99%
“…As these are benthic animals, the high occurrence of acanthocephalans in perch indicates a littoral diet. Perch has a high dependence on the littoral zone (Zamora & Moreno-Amich 2002;Jacobsen et al 2015), and it prefers the littoral zone during spring and summer according to a telemetric study (Westrelin et al 2018).…”
Section: Descriptive Statisticsmentioning
confidence: 99%